English in Workspace: Upaya Meningkatkan Kemampuan Bahasa Inggris di Dunia Kerja Bagi Mahasiswa - Lubaba, Tandday; Utari, Gita; Alfarizi, Muhammad; Dwi Andriani, Zulfi Zumala; Ahimsya, Ahmad Fahim Hilmy (Abdimas Indonesian Journal, 2024)
The "English in Workspace" program is a community service initiative organized by the Tadris Bahasa Inggris (TBIG) program in collaboration with KKN Merdeka 2024 at Universitas KH. Mukhtar Syafa'at Banyuwangi. This two-day seminar aimed to provide students with insights into the importance of English proficiency in professional settings. By involving alumni with successful careers in various industries such as education, content creation, and international business, the seminar offered practical strategies for integrating English skills into the workplace. Through need assessments, it was identified that students lacked awareness of how English could enhance their career prospects. The seminar addressed this gap by presenting real-world applications of English in fields like business negotiation, content editing, and corporate communication. The results showed a significant increase in students’ motivation and readiness to improve their English skills. This initiative highlights the role of academic institutions in supporting the Tri Dharma Perguruan Tinggi, particularly in preparing students for the competitive global job market